The Mormon cult a former missionary reveals the secrets of Mormon mind control - Worthy, Jack B. (Tucson, Ariz. : See Sharp Press, 2008)
This book describes the author's work as a missionary in Hong Kong and his experience working in the cinema in Hong Kong after being excommunicated. The author reveals Mormonism's inherent racism and sexism as displayed in official church documents, including the Book of the Mormon and proclamations by the church's prophets.
A thumbnail history of Mormonism -- The indoctrination process -- Life before my mission -- My mission in Hong Kong -- Excommunication and life after Mormonism.
Introduction by Richard Packham.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mormon Church -- China -- Hong Kong; Motion pictures -- China -- Hong Kong; Mormon Church -- Controversial literature; Mormons -- Biography; Mormon Church; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Christianity -- Church of Jesus Christ of Latter-day Saints (Mormon); Electronic books